Corporate blogging in Singapore - Bay, Hui Yun (2009)
This research looks at the corporate blogging scene in Singapore – an area that is relatively unexplored. In particular, we examined 1) the reasons why consumers are attracted to a blog and 2) the visual elements (e.g. background colour) in the blog which attracts consumers.